(untitled) (American Journal of Business Management, Economics and Banking, 2023)
In this article, the main task of public-private partnership is the effective interaction of public and private partners for the stable socio-economic development of Uzbekistan, and the main mechanisms for attracting private investments at the expense of attracting public and private partner’s resources to the economy. Opinions of foreign and local scientists are given on the term private partnership. Also, the article presents the practice of establishing a public-private partnership in the world experience and the analysis of projects financed on the basis of public-private partnership in Uzbekistan.